2017
DOI: 10.1007/s11751-017-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infected non-unions with segmental defects with a rail fixation system

Abstract: We conducted this study to evaluate the use of rail fixation system in infected gap non-union of femur and tibia as an alternative to the established Ilizarov circular fixator technique. Prospective study. The study was done in the Department of Orthopaedic surgery in a medical school and level I trauma center to which the authors are/were affiliated. Between June 2010 and June 2015, 40 patients with infected gap non-union of femur and tibia were treated with the rail fixation system. Patients who were willing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
2
6
0
2
Order By: Relevance
“…Our study was exclusively for treatment of infected nonunion. Our study was comparable with Arora et al ,13 Pal et al ,4 Mudiganty et al 23 and Seenappa et al 14 as rail fixator was more comfortable to patients compared to Ilizarov [Tables 4 and 5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study was exclusively for treatment of infected nonunion. Our study was comparable with Arora et al ,13 Pal et al ,4 Mudiganty et al 23 and Seenappa et al 14 as rail fixator was more comfortable to patients compared to Ilizarov [Tables 4 and 5].…”
Section: Discussionsupporting
confidence: 90%
“…Infection itself is a great factor for the increased time of treatment. According to modified ASAMI classification, the results of the present study were compared with other studies 46131416202223. There was no statistically significant difference in bone and functional results between the two groups.…”
Section: Discussionmentioning
confidence: 58%
“…The methods used for skeletal stabilization for these injuries still remains debated, with several options such as intramedullary rods, bone plates, external fixations, and intramedullary nailing. [12][13][14][15][16][17][18] Donally et al showed 28.6% of incidence of infection in his study for primary nailing in compound tibia fractures, 22% was seen in Henkelmann et al and 25% in Mudiganty et al and 30.3% in Wei et al [19][20][21][22] Smokers had a relatively increased risk of infection and delayed wound healing in other studies, 24.7% has been documented by Hao et al 22 In our review, personal habits such as smoking, substance abuse and comorbidities such as diabetes and hypertension were not discussed. Operative duration didn't influence significantly in infection rate and there was no significant difference in timing of surgery among these references.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of mu rhythm is about 10 Hz, if classified according to frequency and amplitude, it can be classified as α wave, but mu rhythm has nothing to do with the state of eye closure, it is a kind of EEG signal which is closely related to somatic motor area. B waves are distributed near the frontal lobe and central sulcus, but the β waves related to mu rhythm often appear near the central sulcus (Mudiganty et al, 2017;Torres-Rodríguez et al, 2018;van Yperen et al, 2018). Therefore, in the study of BCI, we usually focus on the β waves near the central sulcus.…”
Section: Physiological Basis Of Brain-computer Interfacementioning
confidence: 99%